(3MeGjI GdeSJgdc (B:s (3OQGSI ebGQfI (B/s - (3GHQGgje, YHO GdefYe ehSis ((3HjQhJ(B: s (3efThQGJ GdMdHj(B, s, 2007)
(3OQGSI GdfUhU GdGJLGgGJ GdJbdjOjI dMeGjI GdeSJgdc GdMeGjI GdYGeI ddeSJgdc , GdfUhU GdOhdjI hGdeOfjI hMeGjI GdeSJgdc , GdfUhU GdLRGFjI hMeGjI GdeSJgdc GdMeGjI ZjQ eHGTQI ddeSJgdc , GdMeGjI GdafjI hGdegfjI ddeSJgdc , GdMeGjI GdGLRGFjI ddeSJgdc (B-(3GdGJLGgGJ GdMOjKI dMeGjI GdeSJgdc hgd jecf GdGNP HgG aj cd ef GdJTQYjjf GddHfGfj hGdShOGfj MeGjI GdeSJgdc aj aJQI Jchjf GdYbO , MSf GdfjI hMeGjI GdeSJgdc ,MeGjI GdMQjI GdJYGbOjI ddeSJgdc MeGjI GdeSJgdc aj aJQI JfajP GdYbO , VeGfGJ MeGjI GdeSJgdc , GdeSDhdjI GdYbOjI chSjdI dVeGf SdGeI GdeSJgdc s
(3HjHdjhZQGajG U(B.591(3; edGMb U(B.607 s
Keywords: (3GOGQIs; (3GdeSJgdc bhGfjf hJTQjYGJs; (3MeGjI GdeSJgdcs; (3UfGYIs